PENINGKATAN KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN MELALUI PENDEKATAN WHOLE LANGUAGE DI TK KELOMPOK B - Ita Apriliyani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2017)
as two cycles in the first cycle as many as 8 meetings and cycle II as many as 4 times the meeting. The purpose of this study is expected to increase children’s ability to listen using Whole Language method in which there are elements of memory, writing, reading and speaking. Based on the results of the research, the ability to listen to children aged 5-6 years through the method of intact language with the results of this study on the initial condition of 23% and then in the first cycle increased to 50%, in the second cycle had a significant increase reached 78% and experienced success in the indicator which already applies. Based on the results of data that have been obtained it can be concluded that the research conducted by appasil by applying Whole Language method can improve the ability to listen to children aged 5-6 years in TK Kemala Bhayangkari 4 Kota Serang.